A macro view of Bionanotechnology: Application and implications in the near future - Chan, Stephanie; Don, M. (2011)
To biologists, bionanotechnology refers to engineered nanostructures and nanomachines or naturally occurring cell machinery with biological molecules such as proteins, peptides, DNA, RNA in a living organism. Over the past 30 years biotechnologists have been working intensively in the medical and pharmaceutical areas; however, the term bionanotechnology have found its place recently in the areas of electronic, agricultural, food, and cosmetics. This is due to the increase awareness of biocompability, sustainability and environmental issues. In addition, some thought is given to the economic challenges that bionanotechnology may produced. This paper reviews the expanding bionanotechnology branches used currently, and also the future prospect that bionanotechnology could achieve in various applications.